Critically important antibiotics: criteria and approaches for measuring and reducing their use in food animal agriculture. Issue 1 (29th March 2019) - Scott, H. Morgan; Acuff, Gary; Bergeron, Gilles; Bourassa, Megan W.; Gill, Jason; Graham, David W.; Kahn, Laura H.; Morley, Paul S.; Salois, Matthew Jude; Simjee, Shabbir; Singer, Randall S.; Smith, Tara C.; et al.
Abstract: Globally, increasing acquired antimicrobial resistance among pathogenic bacteria presents an urgent challenge to human and animal health. As a result, significant efforts, such as the One Health Initiative, are underway to curtail and optimize the use of critically important antimicrobials for human medicine in all applications, including food animal production. This review discusses the rationale behind multiple and competing "critically important antimicrobial" lists and their contexts as created by international, regional, and national organizations; identifies discrepancies among these lists; and describes issues surrounding risk management recommendations that have been made by regulatory organizations on the use of antibiotics in food animal production. A more harmonized approach to defining criticality in its various contexts (e.g., for human versus animal health, enteric diseases versus other systemic infections, and direct versus indirect selection of resistance) is needed in order to identify shared contextual features, aid in their translation into risk management, and identify the best ways to maintain the health of food animals, all while keeping in mind the wider risks of antimicrobial resistance, environmental impacts, and animal welfare considerations. Abstract : Most of the antibiotics sold for animal use in the US are either not considered medically important by the FDA (e.g., ionophores) or else are not included in the list of critically important antimicrobials for human medicine by the WHO (e.g., tetracyclines). Most of the highest priority critically important antimicrobials (HPCIA) have relatively low sales volumes (e.g., fluoroquinolones and cephalosporins), the exception to this being the macrolide class.